Abdominal aorta aneurysm with hostile neck: Early outcomes in outside instruction for use in patients using the treovance® stent graft - Rossi, Umberto G; Torcia, Pierluca; Dallatana, Raffaello; Santuari, Davide; Mingazzini, Pietro; Cariati, Maurizio (Indian Journal of Radiology and Imaging, 2017)
Purpose: The efficacy and safety of endovascular aneurysm repair (EVAR), in patients outside instruction for use (IFU), is very challenging and widely debated. The aim of this study was to evaluate the placement of the Treovance® abdominal aorta stent-graft in patients with hostile proximal necks considered outside IFU. Materials and Methods: Between May 2013 and August 2014, 5 patients with outside IFU underwent EVAR with the Treovance® stent-graft. Technical and clinical successes were evaluated. All 5 patients underwent clinical and imaging follow-up. Results: Technical and clinical successes were achieved in all 5 patients without adjunctive endovascular procedures or surgical conversion. During the mean follow-up of 21 months, no type I/III endoleaks, stent-graft migration nor kinking/occlusion were observed. In all 5 patients, a reduction of the proximal neck angle was observed. Conclusion: In our small series of selected outside IFU patients, EVAR with the Treovance® stent-graft was technically feasible and safe, with satisfactory short-term follow-up results, when performed by experienced operators. Long-term follow-up will be necessary to confirm the durability of our preliminary promising results.
Keywords: Abdominal aortic aneurysm; endovascular aneurysm repair; instruction for use; proximal aortic neck; Treovance® stent-graft